Technology‐Enhanced Stepped Collaborative Care Targeting Posttraumatic Stress Disorder and Comorbidity After Injury: A Randomized Controlled Trial. Issue 5 (14th October 2015) - Zatzick, Douglas; O'Connor, Stephen S.; Russo, Joan; Wang, Jin; Bush, Nigel; Love, Jeff; Peterson, Roselyn; Ingraham, Leah; Darnell, Doyanne; Whiteside, Lauren; Van Eaton, Erik
Abstract: Posttraumatic stress disorder (PTSD) and its comorbidities are endemic among injured trauma survivors. Previous collaborative care trials targeting PTSD after injury have been effective, but they have required intensive clinical resources. The present pragmatic clinical trial randomized acutely injured trauma survivors who screened positive on an automated electronic medical record PTSD assessment to collaborative care intervention ( n = 60) and usual care control ( n = 61) conditions. The stepped measurement‐based intervention included care management, psychopharmacology, and psychotherapy elements. Embedded within the intervention were a series of information technology (IT) components. PTSD symptoms were assessed with the PTSD Checklist at baseline prerandomization and again, 1‐, 3‐, and 6‐months postinjury. IT utilization was also assessed. The technology‐assisted intervention required a median of 2.25 hours (interquartile range = 1.57 hours) per patient. The intervention was associated with modest symptom reductions, but beyond the margin of statistical significance in the unadjusted model: F (2, 204) = 2.95, p = .055. The covariate adjusted regression was significant: F (2, 204) = 3.06, p = .049. The PTSD intervention effect was greatest at the 3‐month (Cohen's effect size d = 0.35, F (1, 204) = 4.11, p = .044) and 6‐month ( d = 0.38, F (1, 204) = 4.10, p = .044) time points. IT‐enhanced collaborative care was associated with modest PTSD symptom reductions and reduced delivery times; the intervention model could potentially facilitate efficient PTSD treatment after injury.